2016
DOI: 10.1371/journal.pone.0150696
|View full text |Cite
|
Sign up to set email alerts
|

The BH3 Mimetic Obatoclax Accumulates in Lysosomes and Causes Their Alkalinization

Abstract: Obatoclax belongs to a class of compounds known as BH3 mimetics which function as antagonists of Bcl-2 family apoptosis regulators. It has undergone extensive preclinical and clinical evaluation as a cancer therapeutic. Despite this, it is clear that obatoclax has additional pharmacological effects that contribute to its cytotoxic activity. It has been claimed that obatoclax, either alone or in combination with other molecularly targeted therapeutics, induces an autophagic form of cell death. In addition, obat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 44 publications
2
38
0
1
Order By: Relevance
“…Our data, however, significantly extend these findings, providing a defined mechanistic framework for Obatoclax-induced lysosomal damage and cell necrosis. Stamelos and co-workers have recently found that Obatoclax accumulates into lysosomes of ovarian cancer cells, leading to their alkalization [50], providing an independent corroboration of our data. However, in contrast to our findings, apoptosis appeared to be the primary cause of cell death in several of the cell lines analyzed, and in general cell death occurred late, after 48 to 72 hours from Obatoclax treatment, while we show evidence of necrosis in thyroid cancer cells as early as six hours post-treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Our data, however, significantly extend these findings, providing a defined mechanistic framework for Obatoclax-induced lysosomal damage and cell necrosis. Stamelos and co-workers have recently found that Obatoclax accumulates into lysosomes of ovarian cancer cells, leading to their alkalization [50], providing an independent corroboration of our data. However, in contrast to our findings, apoptosis appeared to be the primary cause of cell death in several of the cell lines analyzed, and in general cell death occurred late, after 48 to 72 hours from Obatoclax treatment, while we show evidence of necrosis in thyroid cancer cells as early as six hours post-treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, three recent reports have provided independent corroboration of our findings and showed that OLX not only increases the lysosomal pH but also accumulates in the lysosomes and causes a loss of lysosomal function (37)(38)(39). The fact that OLX is a weak base and the likelihood that it is protonated and accumulates in lysosomes, similar to another lysomotrophic agent, chloroquine, suggest a possible mechanism for the rapid elevation in the lysosomal pH (38). Additionally, Champa et al have suggested that OLX could mediate the exchange of Cl Ϫ and HCO 3 Ϫ ions between the cytoplasm and the lysosome, which would also cause a rapid elevation in the lysosomal pH (37).…”
Section: Discussionsupporting
confidence: 83%
“…Modulation of autophagy is evaluated as a promising therapeutic approach for many diseases such as neurodegenerative disorders, metabolic disease, or cancer . Modulation of autophagy has been described for prodigiosin ( 2 ), for prodidiosin derivatives with different chain lengths, and for obatoclax mesylate (GX15‐070), a synthetic derivative investigated in several phase II clinical trials . The key cellular structures of autophagy are autophagosomes, double‐layer membrane vesicles that receive input from the endocytic pathway.…”
Section: Resultsmentioning
confidence: 99%